2000
DOI: 10.1089/107999000312379
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Post-Golgi Trafficking of Tumor Necrosis Factor-alpha in Macrophages

Abstract: Tumor necrosis factor-alpha (TNF-alpha) is a proinflammatory cytokine secreted by activated macrophages. In this study, we examined the intracellular distribution and trafficking of TNF-alpha. Immunofluorescence and immunogold localization demonstrated that in lipopolysaccharide (LPS)-stimulated RAW264 macrophages, the greatest concentration of TNF-alpha is found in the perinuclear Golgi complex. Staining of the Golgi complex appeared 20 min after activation of cells and persisted for 2-12 h, and TNF-alpha app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
113
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 49 publications
12
113
0
3
Order By: Relevance
“…Additionally, in monocytes it has been demonstrated that pro-TNF-␣ normally has a relatively short half-life of approximately 15 minutes, but in the presence of inhibitor its half-life in cell extracts is extended for up to one hour (Solomon et al, 1997). However, our pulse-chase and immunofluorescence studies in RAW macrophages show that pro-TNF-␣ has a half-life of at least 30 minutes under physiologic conditions (Shurety et al, 2000). Furthermore, in inhibitor-treated macrophages a significant pool of pro-TNF-␣ is retained for much longer times on the surface and in endosomes.…”
Section: Shurety Et Almentioning
confidence: 68%
See 4 more Smart Citations
“…Additionally, in monocytes it has been demonstrated that pro-TNF-␣ normally has a relatively short half-life of approximately 15 minutes, but in the presence of inhibitor its half-life in cell extracts is extended for up to one hour (Solomon et al, 1997). However, our pulse-chase and immunofluorescence studies in RAW macrophages show that pro-TNF-␣ has a half-life of at least 30 minutes under physiologic conditions (Shurety et al, 2000). Furthermore, in inhibitor-treated macrophages a significant pool of pro-TNF-␣ is retained for much longer times on the surface and in endosomes.…”
Section: Shurety Et Almentioning
confidence: 68%
“…Endocytosis and recycling of pro-TNF-␣ is a possible mechanism for modulating levels and functions of surface exposed TNF-␣ and of TNF-␣ available for cleavage. In support of this concept, we have previously shown that macrophages activated by the distinct cascades associated with either LPS and interferon-␥ or LPS alone have different trafficking of TNF-␣ (Shurety et al, 2000). Interferon-␥ induces the trafficking of some TNF-␣ to endosomal structures that may be used to sequester or reroute surface TNF-␣ to produce a different biological action.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations